Potential Nociceptive Regulatory Effect of Probiotic Lactobacillus rhamnosus PB01 (DSM 14870) on Mechanical Sensitivity in Diet-Induced Obesity Model - Fereshteh Dardmeh; Hans Ingolf Nielsen; Hiva Alipour; Benedict Kjærgaard; Erik Brandsborg; Parisa Gazerani (Pain Research and Management)
Treatments for obesity have been shown to reduce pain secondary to weight loss. Intestinal microbiota, as an endogenous factor, influences obesity and pain sensitivity but the effect of oral probiotic supplementation on musculoskeletal pain perception has not been studied systematically. The present study examined the effect of a single daily oral dose (1 × 109 CFU) of probiotics (Lactobacillus rhamnosus PB01, DSM14870) supplement on mechanical pain thresholds in behaving diet-induced obese (DIO) mice and their normal weight (NW) controls. The mice (N=24, 6-week-old male) were randomly divided into four groups on either standard or high fat diet with and without probiotic supplementation. Both DIO and NW groups with probiotic supplementation maintained an insignificant weight gain while the control groups gained significant weight (P<0.05). Similarly, both DIO and NW probiotics supplemented groups demonstrated a significantly (P<0.05) lower sensitivity to mechanical stimulation compared to their corresponding control. The results of this study suggest a protective effect of probiotics on nociception circuits, which propose a direct result of the weight reduction or an indirect result of anti-inflammatory properties of the probiotics. Deciphering the exact underlying mechanism of the weight loss and lowering nociception effect of the probiotic applied in this study require further investigation.